Differences in Work-Life Balance, Flexible Time Arrangement, and Life Satisfaction of Employees of the Ombudsman of the Republic of Indonesia According to Education Level - Rinny Dharma Diani; Sri Indah Nikensari; Agung Wahyu Handaru (Journal of Social Research, 2023)
This research aims to determine the differences in Work-Life Balance, Flexible Time Arrangement, and Life Satisfaction of Indonesian Ombudsman employees according to education level. This research uses a quantitative research approach. The research population used was the Ombudsman of the Republic of Indonesia, while the sample used was 102 employees. The sampling technique uses random sampling for employees who have a high school, diploma, bachelor's degree, level II and level III educational background. The data analysis technique uses the Statistical Package for the Social Sciences (SPSS) application with Two Way ANOVA to test the research hypothesis. The results of this research show that there is no difference in employee work-life balance according to education level, indicated by sig, 0.245>0.05, There is a difference in employee flexible time arrangements according to education level, indicated by p-value 0.030 <0.05, There is a difference in life satisfaction employees according to education level, indicated by a p-value of 0.024 <0.05. Recommendations for further research should be to conduct more research to gain more information and look for solutions to strengthen the life satisfaction of RI Ombudsman employees which can be encouraged with flexible time arrangements so that work-life balance can be carried out well and appropriately in the work of each employee.